Revisión del campo de las políticas públicas desde la óptica de los estudiosos mexicanos - Moreno Jaimes, Carlos (El Colegio de México A.C., 2024)
In this article, it is argued that public policy studies found fertile ground in Mexico upon their arrival in the early 1990s. They stimulated Mexican scholars to discuss two notions that had been taken for granted in Western countries, but that turned out to be novel concepts in Mexico: policy-oriented governance and governing the public interest. The policy field in Mexico made further progress by considering three features that characterize the country’s political and administrative background. First, the salience of the State as the most important policymaking actor, which, paradoxically, lacks the institutional capacities to become a more effective one. Second, informal rules inherited from Mexico’s authoritarian period still strongly influence the behavior of people and organized groups. Finally, social inequality influences Mexico’s policymaking by demobilizing social sectors that could act in favor of the poor, preventing governments from enforcing the law, or letting street-level bureaucracies apply selective enforcement criteria in discretionary ways.